2006
DOI: 10.1002/app.25218
|View full text |Cite
|
Sign up to set email alerts
|

Submicrometer characterization of surfaces of epoxy‐based organic–inorganic nanocomposite coatings. A comparison of AFM study with currently used testing techniques

Abstract: Surface properties (morphology, hardness) of transparent colorless epoxy-based organic-inorganic nanocomposite coatings were investigated by atomic force microscopy, optical and scanning electron microscopy, nanoindentation, and the Persoz pendulum test. Friction and wear coefficients were obtained from tribological experiments. The influence of mechanical properties and the size, shape, and concentration of additives (colloidal silica particles and montmorillonite sheets) on the measured surface characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The characterization of the structure of nanocomposites Figure 2 illustrated that the solid-state 29 Si-NMR spectra of nanocomposite, which assigned to the T and Q groups of the silsesquioxane characteristic peak. The T and Q structures are shown in Scheme 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characterization of the structure of nanocomposites Figure 2 illustrated that the solid-state 29 Si-NMR spectra of nanocomposite, which assigned to the T and Q groups of the silsesquioxane characteristic peak. The T and Q structures are shown in Scheme 3.…”
Section: Resultsmentioning
confidence: 99%
“…Solid-state 29 Si-NMR analysis was performed with a Bruker DSX 400WB (400 MHz) NMR spectrometer. TGA was conducted with a Thermal Analysis TGA-951 thermogravimetric analyzer at various heating rates (5, 10, 15, 20, and 30 C/min) under nitrogen atmosphere.…”
Section: Characterization and Properties Measurementmentioning
confidence: 99%
“…heterogeneities on nm size with roughness of units nm) were characteristics for O-I matrices without any nanoadditives. 12 The relief of the modified samples (2D and 3D images) shows MMT platelets rising from the O-I matrix (Fig. 5).…”
Section: Surface Topographymentioning
confidence: 96%
“…Colourless and transparent products can be prepared, which are in the glassy, main transition or rubbery state at 23uC (depending on the material and preparation technique used). [8][9][10][11][12] In this contribution, the influence of the concentration of two different commercial montmorillonite platelets, unmodified MMT (i.e. natural MMT containing Na z counter ions in the interlayer), and chemically modified MMT (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Spirkova et al applied several techniques to evaluate surface properties (morphology, hardness, wear) of organic-inorganic nanocomposite coatings prepared from silicon-containing precursors and Jeffamines (119). They indicated that the current AFM methods are applicable not only for the determination of surface topography, but also for the scratch resistance determination.…”
Section: Coupled Applicationsmentioning
confidence: 99%